Productivity Growth in Service Industries An Assessment of Recent Patterns and the Role of Measurement - Wölfl, Anita (OECD Publishing, 2003)
This paper examines recent patterns in productivity growth of service industries and analyses the role of problems in measuring service productivity growth on industry and aggregate productivity growth. At the aggregate level, unbalanced growth can be observed between a dynamic manufacturing sector on one hand and a rather stagnant service sector on the other. The service sector itself is, however, composed of a set of heterogenous industries with productivity growth rates ranging from low or negative rates to growth rates exceeding those of high-growth manufacturing industries. The empirical evidence suggests that low or negative productivity growth rates in several services are linked to measurement problems. Computing constant price service output is particularly important. Potential under-estimation of service productivity growth leads eventually to an under-estimation of aggregate productivity growth, via aggregation effects and the flows of intermediate inputs. There ...
Keywords: Science and Technology